1998
DOI: 10.1007/s002469900338
|View full text |Cite
|
Sign up to set email alerts
|

Complete Left Pericardial Defect with Dual Passage of the Phrenic Nerve: A Challenge to the Widely Accepted Embryogenic Theory

Abstract: We report a patient with complete left pericardial defect whose phrenic nerve, split into two portions, passes both ventral and dorsal to the defect. The dorsal part of the phrenic nerve passes over the ventral surface of the pulmonary artery and veins, indicating that the pericardio-pleural foramen has been obliterated. Contrary to the widely accepted embryogenic theory that pericardial defect results from persistence of the pericardiopleural foramen, we consider that the defect in this patient resulted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Perna (1909) proposed that the premature atrophy of the left duct of Cuvier results from insufficient blood supply to the PPMs 19. Alternatively, altered growth of the heart may inappropriately stretch and tear the PPMs 20. To our knowledge, normal and abnormal pericardial development has not been described in any detail in the mouse.…”
Section: Discussionmentioning
confidence: 95%
“…Perna (1909) proposed that the premature atrophy of the left duct of Cuvier results from insufficient blood supply to the PPMs 19. Alternatively, altered growth of the heart may inappropriately stretch and tear the PPMs 20. To our knowledge, normal and abnormal pericardial development has not been described in any detail in the mouse.…”
Section: Discussionmentioning
confidence: 95%
“…An alternative theory proposes that a traction induced tear may develop in the pleuropericardial membrane, with a resultant pericardial defect. Kaneko et al's case of pericardial absence associated with a divided phrenic nerve,[ 4 ] passing both ventrally and dorsally to the defect, illustrates this conjecture. A third theory attributes the developmental failure of the pericardial membrane to premature atrophy of the cardinal veins (duct of Cuvier) supplying the pleuropericardial folds.…”
Section: Introductionmentioning
confidence: 99%
“…Its persistence may be due to inadequate blood supply following premature atrophy of the left common cardinal vein (the duct of Cuvier), which is an event that could account for both the defect and its tendency to occur on the left side (2). A recent article suggests that some defects may be due to a tear in the pleuro-pericardial membrane rather than failure of the pleuro-pericardial foramen to close (3). …”
Section: Discussionmentioning
confidence: 99%
“…It has rarely been reported that the left phrenic nerve runs behind it (9, 10). Kaneko and associates (3) report a patient with a complete left pericardial defect whose phrenic nerve, split into two portions, passes both ventral and dorsal to the defect. Our case is an example where the phrenic nerve runs behind the defect.…”
Section: Discussionmentioning
confidence: 99%